Effects of Sediment Characteristics on Carbon Dioxide Fluxes Based on Interacting Factors in Unvegetated Tidal Flats - Lin, Wei-Jen; Chiu, Ming-Chih; Lin, Chiao-Wen; Lin, Hsing-Juh (Frontiers in Marine Science, 2021)
The contribution of unvegetated tidal flats to global net primary production is comparable to that of some vegetated coastal habitats. However, compared to carbon flux regulating factors in vegetated habitats, those in unvegetated tidal flats are not well understood, particularly in terms of their cause-effect relationships. Maximum gross primary production (GPPm), net primary production (NPP) and total respiration (TR) during emersion at noon when the irradiance level was at the saturation level for photosynthesis in nine unvegetated tidal flats across the Taiwan Strait in tropical and subtropical regions were determined in winter and summer from 2011 to 2016 to examine the direct and indirect relationships between sediment characteristics and carbon fluxes by using structural equation models (SEM). Most of the GPPm and NPP values were higher in winter than in summer. Conversely, the TR values were higher in summer than in winter. The NPP values at some sites shifted to negative values in summer, indicating the sites were carbon sources. The values of GPPm, TR and NPP for the tidal flats all increased significantly with increasing sediment mud content. The SEM results showed that the sediment mud content directly increased GPPm or indirectly increased GPPm via a compositional shift in benthic microalgae. The sediment mud content also directly increased TR or indirectly increased TR via increased organic matter content. The contribution of benthic microalgal and macrofaunal biomass to TR was relatively minor. This result suggests that primary production was stimulated mainly by the organic matter content rather than by increased microalgal biomass. With the integrated SEM framework, our results showed mechanistic evidence of how sediment mud content acted as a critical factor regulating carbon fluxes in unvegetated tidal flats.